The acquisition of foreign language vocabulary: Does spacing effect matter? - F. M. Al-Khasawneh (Russian State Vocational Pedagogical University, 2023)
Introduction. Research that investigated effective strategies for learning foreign language vocabulary revealed that long spacing facilitates learning more than short or no spacing. This phenomenon is known as distributed practice effect.Aim. The present study aimed to examine the effect of spaced instruction on vocabulary learning and retention among Saudi EFL learners.Methodology and research methods. The sample of this study includes 30 English major students at King Khalid University. The students were divided into two groups (15 students for the massed instruction group and 15 students for the spaced instruction group). Both groups were taught 20 new words which were selected based on the results of the Vocabulary Size Test by Nation P., Beglar D. In the condition of massed class, the target words were taught in 45-minute weekly session (lasted for two weeks). In the condition of spaced class, 45 minutes were distributed into three 15-minutes session presented throughout the week at intervals with two intervening days between each session (lasted for two weeks). Both groups received a post-test after eight weeks of training, while the delayed post-test was administered three weeks later (week 11).Results. The results of the study revealed that there was statistically significant difference between the massed and spaced instruction groups on both post-test and delayed post-test in favor to the spaced instruction group.Scientific novelty. The present study makes several contributions to the body of literature. First, it adds to the relatively small amount of research on the spacing effect on the acquisition of foreign language vocabulary. Second, it is one of the very few studies that have been conducted in the Arab world, more specifically in the Saudi context. Finally, the study provides better understanding of the importance of spacing in learning foreign language vocabulary among Arab learners.Practical significance. In the light of the obtained results, several recommendations have been provided for EFL practitioners and curriculum designers. This study suggests that EFL practitioners should consider spaced learning as beneficial teaching strategy, and to synthesise it in the educational materials.